2020
DOI: 10.12737/stp-61202010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Sun on Earthʼs Seismicity

Abstract: For the experimental study of the relationship between earthquakes and solar activity, we introduce the idea of the statistical sum Z of earthquake ensemble. A number of numerical parameters of seismicity (average planetary magnitude, entropy, fluctuations of magnitude) are expressed through Z. A severe restriction is, however, imposed on the magnitude during the formation of the ensemble. We propose an alternative method. It does not have this specific restriction, although it allows us to calculate only one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The stimulation of energy low focuses was illustrated by Guglielmi et al [39]; by using the widespread indices, the Wolf numbers W, to characterize solar activity the authors have found the certain relationship between earthquakes and solar activity. The global daily magnitudes M g , calculated over the 20-year period from 1980 to 1999, were correlated with daily W numbers; the pairs M g −W are shown in Figure 2.…”
Section: Magnetically Controlled Seismicitymentioning
confidence: 99%
“…The stimulation of energy low focuses was illustrated by Guglielmi et al [39]; by using the widespread indices, the Wolf numbers W, to characterize solar activity the authors have found the certain relationship between earthquakes and solar activity. The global daily magnitudes M g , calculated over the 20-year period from 1980 to 1999, were correlated with daily W numbers; the pairs M g −W are shown in Figure 2.…”
Section: Magnetically Controlled Seismicitymentioning
confidence: 99%
“…The idea that space weather-as measured by sunspots, cosmic rays, solar wind, interplanetary magnetic fields, geomagnetic activity, and precipitation of charged particles from the radiation belt-may play a role in triggering earthquakes has a long history but has not received physical justification for the time being. It was noted in [1] that the problem's difficulty is that the unknown is a physical mechanism of action involving relatively weak fields of cosmic origin on tectonic processes. The authors of [2] suggested that geomagnetic variations affect rocks, e.g., by inducing eddy currents in the Earth's crust via an alternating magnetic field, leading to rocks' additional heating.…”
Section: Introductionmentioning
confidence: 99%
“…The GEC links the electric fields and currents flowing in different parts of the atmosphere [12,13]. There are three main generators of fields and currents in the global electric circuit [13]: (1) the troposphere generator (continuous thunderstorm activity of the Earth, with about 46 lightning strikes per second); (2) the ionospheric wind dynamo; and (3) the solar wind/magnetosphere dynamo. The troposphere generator may provide a 200 kV to 600 kV potential difference between the ground and the ionosphere.…”
Section: Introductionmentioning
confidence: 99%